2023
DOI: 10.3390/ijerph20021604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Perceptions, Preferences, and Participation Intention of Urban Forest Healing Program among Cancer Survivors

Abstract: It is important to manage the health of cancer survivors who have returned to their daily lives. An increasing number of cancer survivors are undertaking health care in forests near their residences. This cross-sectional study aimed to determine the perceptions of forest healing and the program preferences of adult cancer survivors. Data were collected from 388 female cancer survivors through an online survey. Breast cancer survivors comprised 66.2%, and 63.6% of the study participants were diagnosed with canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A similar study reported that preoperative negative emotions, including anxiety, depression, and anger, were positively associated with the severity of POF in inpatients after surgery [33][34][35] . Previous studies have indicated preoperative anxiety can increase the release of proin ammatory factors and stimulate hypothalamus-pituitary-adrenalin (HPA) axis by enhancing the endocrine and immune responses induced by surgery, while dysfunction of HPA axis often exacerbates patients' POF through various signaling pathways [36,37] . This may offer an explanation for our ndings.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study reported that preoperative negative emotions, including anxiety, depression, and anger, were positively associated with the severity of POF in inpatients after surgery [33][34][35] . Previous studies have indicated preoperative anxiety can increase the release of proin ammatory factors and stimulate hypothalamus-pituitary-adrenalin (HPA) axis by enhancing the endocrine and immune responses induced by surgery, while dysfunction of HPA axis often exacerbates patients' POF through various signaling pathways [36,37] . This may offer an explanation for our ndings.…”
Section: Discussionmentioning
confidence: 99%